Case Report: Prurigo nodularis-like linear IgA/IgG bullous dermatosis: a case report and literature review - Zhou, Yuxi; Zhou, Xingli; Feng, Xun; Xia, Dengmei; Qian, Hua; Liu, Hongjie; Li, Xiaoguang; Li, Wei (Frontiers in Immunology, 2023)
Linear IgA/IgG bullous dermatosis (LAGBD) is a rare autoimmune subepidermal bullous disorder characterized by linear deposition of concurrent IgA and IgG autoantibodies along the basement membrane zone (BMZ). The clinical features of LAGBD can be diverse, including tense blisters, erosions, erythema, crusting and mucosa involvement, while papules or nodules are generally absent. In this study, we present a unique case of LAGBD, which showed prurigo nodularis-like clinical appearance on physical examination, linear deposition of IgG and C3 along the basement membrane zone (BMZ) in direct immunofluorescence (DIF), IgA autoantibodies against the 97-kDa and 120-kDa of BP180 and IgG autoantibodies against the 97-kDa of BP180 by immunoblotting (IB), while BP180 NC16a domain, BP230, and laminin 332 were negative by enzyme-linked immunosorbent assay (ELISA). After administration of minocycline, the skin lesions improved. We performed a literature review of LAGBD cases with heterogeneous autoantibodies and found clinical presentations of most cases resemble bullous pemphigoid (BP) and linear IgA bullous disease (LABD), which is consistent with previous reported findings. We aim to increase our understanding of this disorder and to enhance the importance of applying immunoblot analyses and other serological detection tools in clinic for precise diagnosis as well as accurate treatment strategy of various autoimmune bullous dermatoses.